A GIS-based method to identify potential sites for pumped hydro energy storage - Case of Iran. (15th February 2019) - Ghorbani, Narges; Makian, Hamed; Breyer, Christian
Abstract: Pumped hydro energy storage (PHES) is the most widespread and mature utility-scale storage technology currently available and it is likely to remain a competitive solution for modern energy systems based on high penetration of solar PV and wind energy. This study estimates the technical potential of PHES in Iran through automatised GIS-based models based on four topologies. Two topologies focus on the transformation of existing reservoirs while the third topology which is developed based on permanent rivers of the country offers more alternative sites. The fourth topology assesses the potential of seawater PHES plants as a potential solution for regions characterised by freshwater scarcity. The TOPSIS method is applied to the discovered feasible sites to integrate an economic sensitivity into the evaluation process. Results show that Iran has a favourable topography for PHES and the technical potential of the studied topologies reaches up to 5108 GWh from 250 discovered sites, compared to the existing 5.1 GWh PHES capacity, while a maximum distance of 20 km is considered between reservoirs of a PHES plant. Highlights: Comprehensive new methodology for PHES potential assessment developed. Technical potential of PHES in Iran is 1000 times higher than the existing capacity. Southwest of Iran provides the highest PHES potential and the most suitable sites. Substantial potential for covering short-term storage demand in 2050.